2010
DOI: 10.1016/j.jtcvs.2010.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular valve repair in patients with functional single ventricle

Abstract: The midterm results of atrioventricular valve repair in patients with functional single ventricle were favorable; however, young and small patients, especially those with hypoplastic left heart syndrome, still had poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 26 publications
3
22
0
Order By: Relevance
“…The Toronto team demonstrated that up to 60% of the patients with right atrial isomerism and one-half of those with left atrial isomerism will die before reaching Fontan status (17)(18)(19). Meanwhile, studies have shown that atrioventricular valve regurgitation before the time of BCPS was associated with increased mortality, particularly among patients with HLHS (20,21). Finally, it was not surprising to note that the prognosis of our patients without transposition was better, as they clearly gathered a larger proportion of patients with dominant left ventricles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Toronto team demonstrated that up to 60% of the patients with right atrial isomerism and one-half of those with left atrial isomerism will die before reaching Fontan status (17)(18)(19). Meanwhile, studies have shown that atrioventricular valve regurgitation before the time of BCPS was associated with increased mortality, particularly among patients with HLHS (20,21). Finally, it was not surprising to note that the prognosis of our patients without transposition was better, as they clearly gathered a larger proportion of patients with dominant left ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…We defined neonatal palliation as one of the following procedures: Norwood operation, systemic-pulmonary shunt, pulmonary artery banding procedure, Damus-KayeStansel connection, attempted biventricular repair, total anomalous pulmonary venous drainage repair, or arterial Patient Characteristics According to Era Extracardiac defects 87 (17) 37 (14) 50 (21) Dominant diagnosis…”
Section: Methodsmentioning
confidence: 99%
“…The exact survival was not unclear, but the diagnosis of HLHS was significantly associated with worse outcome, and overall 1-year survival was approximately 40% following valve repair. 32 Honjo et al 9 reported a series of 57 patients with atrioventricular valve plasty for single-ventricle physiology; 67% of the valves were tricuspid. Survival in the repair group was lower than in the matched controls (78.9% vs. 92.7% at 1 year; 68.7% vs. 90.6% at 3 years, P=0.015).…”
Section: Results Of Tv Repairmentioning
confidence: 99%
“…A similar principle was also advocated by Sakamoto et al for repairing atrioventricular valves in patients with a single ventricle. 32 If patients require TVP in the later stage (BDG shunt or TCPC), we performed more leaflet repair in addition to the annulus-commissuroplication technique.…”
Section: Survival Analysismentioning
confidence: 99%
“…Multiple reports have demonstrated that tricuspid valve repair before the stage II operation is associated with high mortality and failure risk and frequent deterioration in systemic right ventricular function. [8][9][10] Tricuspid valve repair is therefore commonly reserved for those with failed recovery after the stage I operation, and it would be unlikely for surgeons to attempt tricuspid valve surgery in neonates with moderate to severe tricuspid valve regurgitation who are thriving and otherwise candidates for hospital discharge. Continuous hospitalization until the stage II operation and early listing of proper candidates for heart transplantation might be a consideration in those cases.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 99%